2013
DOI: 10.3892/or.2013.2695
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated IL-24 expression enhances the chemosensitivity of multidrug-resistant gastric cancer cells to cisplatin

Abstract: Abstract. Chemotherapy is one of the commonly used strategies in gastric cancer, especially for unresectable patients, but it becomes insensitive to repeated administration of even the most effective chemotherapeutic agents, such as cisplatin. Given this, there is an urgent need for developing chemosensitizers to overcome acquired resistance to chemotherapeutic agents. Interleukin-24 (IL-24), a cytokine-tumor suppressor, shows broad-spectrum and tumor-specific antitumor properties, and studies have demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…MDR compromises the efficacy of chemotherapy in clinical treatment, and therefore, eliminating MDR of cancer cells is urgently required for improving outcomes. IL-24 has been demonstrated to reverse the MDR phenotype of colon cancer (16), gastric carcinoma (17) and hepatoma (18), possibly by decreasing the expression of Pgp (16). Oncolytic adenovirus-mediated IL-24 expression also suppressed the resistance…”
Section: Discussionmentioning
confidence: 99%
“…MDR compromises the efficacy of chemotherapy in clinical treatment, and therefore, eliminating MDR of cancer cells is urgently required for improving outcomes. IL-24 has been demonstrated to reverse the MDR phenotype of colon cancer (16), gastric carcinoma (17) and hepatoma (18), possibly by decreasing the expression of Pgp (16). Oncolytic adenovirus-mediated IL-24 expression also suppressed the resistance…”
Section: Discussionmentioning
confidence: 99%
“…EGF (epidermal growth factor) 17 , VEGF (vascular endothelial growth factor) 18 and HGF (hepatocyte growth factor) 19 have significant effects on oncogenesis, and they have been developed as targets for tumor therapy. On the other hand, some cytokines function as tumor suppressors, preventing and suppressing the development of cancer 20 , such as oncostatin M (OSM) 21 and interleukin-24 (IL-24) 22 . OSM is a multifunctional interleukin 6-related cytokine, which inhibits the proliferation of various solid tumor cell lines.…”
mentioning
confidence: 99%
“…In addition, Ad-IL-24 was related to up-regulation of Bax and down-regulation of p -gp and Bcl-2 in SGC7901/CDDP cells in vitro and in vivo. Consequently, these studies indicated that overexpression of the IL-24 gene can significantly promote chemosensitivity in GC cells with the MDR SGC7901/CDDP phenotype [ 45 ] ( Table 1 , Figure 1 ). These are the only studies on the role of IL-24 in the mechanisms of chemoresistance in GC.…”
Section: The Role Of Interleukins In the Mechanism Of Chemoresistance...mentioning
confidence: 99%